The role of amino acid and mono potassium phosphate (MKP) fertilizer on the growth of tendrils and flower buds of yellow dragon fruit - Sakinah, Ni'mawati; Hadi, Ahmad; Suprandono, Edi; Putra, Guntur Riyan Kusuma; Said, Ahmad Muthi' Nur; Sholehudin, Abdul Wahid (Universitas Muhammadiyah Mataram, 2025)
This study aimed to investigate the effect of amino acid and Mono Potassium Phosphate (MKP) application on shoot growth and flower bud initiation of yellow pitaya (Hylocereus megalanthus), Naning wangi. The experiment was conducted at the P4S Suka Tani experimental field, Banyuwangi, off season, using a factorial randomized block design (RBD) with two treatment factors: amino acid concentrations and MKP application. Amino acids were applied through foliar spraying, while MKP was applied via soil fertilization at seven-day intervals. Observed parameters included the number of shoots and flower buds. The results showed that amino acid treatments, either alone or in interaction with MKP, had no significant effect on shoot number at the early stage (7 DAA), although a positive trend was observed in subsequent observations. MKP application significantly affected shoot growth at 14 DAA, with the concentration of 4 g/L (K3) producing the highest number of shoots. For flower bud initiation, MKP significantly increased bud formation after 21 DAA, particularly at 4 g/L, which showed a higher number of buds compared to other treatments. Meanwhile, amino acid application did not show a significant effect on flower bud formation. Overall, this study demonstrates that MKP fertilizer plays an important role in enhancing vegetative growth and stimulating the generative phase of yellow dragon fruit, whereas amino acid application did not provide a significant contribution under the tested conditions. These findings offer useful insights for developing cultivation techniques to improve yellow dragon fruit productivity.